2020
DOI: 10.1177/1747021820978851
|View full text |Cite
|
Sign up to set email alerts
|

Veracity judgement, not accuracy: Reconsidering the role of facial expressions, empathy, and emotion recognition training on deception detection

Abstract: People hold strong beliefs about the role of emotional cues in detecting deception. While research on the diagnostic value of such cues has been mixed, their influence on human veracity judgments is yet to be fully explored. Here, we address the relationship between emotional information and veracity judgments. In Study 1, the role of emotion recognition in the process of detecting naturalistic lies was investigated. Decoders’ veracity judgments were compared based on differences in trait empathy and their abi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 105 publications
0
22
0
Order By: Relevance
“…Importantly, micro expressions did not occur more frequently in deceptive scenarios, although the frequency of deception detection due to inconsistent expressions was significantly above chance. Zloteanu et al ( 2021 ) found a generally high micro expression ERA among their participants, but this was not related to accuracy in judging true or false statements and there was no effect of micro expression training on deception detection. Jordan et al ( 2019 ) likewise found no evidence that micro expression training improves detection of deception.…”
Section: Introductionmentioning
confidence: 81%
“…Importantly, micro expressions did not occur more frequently in deceptive scenarios, although the frequency of deception detection due to inconsistent expressions was significantly above chance. Zloteanu et al ( 2021 ) found a generally high micro expression ERA among their participants, but this was not related to accuracy in judging true or false statements and there was no effect of micro expression training on deception detection. Jordan et al ( 2019 ) likewise found no evidence that micro expression training improves detection of deception.…”
Section: Introductionmentioning
confidence: 81%
“…However, the literature on the emotion-based approach to lie detection is highly contentious [36,38]. While some studies indicate that, in specific scenarios, the ability to detect microexpressions is positively related to deception detection performance [39,40], more recent evaluations find no link between emotional cues and improvements in accuracy [41,42].…”
Section: Facial Expressionsmentioning
confidence: 99%
“…If the posture manipulation has an effect on social acuity, a difference in facial expression recognition ability may be most evident. Second, while the evidence on the relationship between microexpression and deception detection is mixed (especially regarding human judges; [42]), people do hold strong beliefs that facial expressions are diagnostic of deceit [32,35]. If judges in a specific posture show a difference in veracity judgments (beneficial or otherwise), an overreliance on facial cues may explain the effect.…”
Section: Facial Expressionsmentioning
confidence: 99%
See 2 more Smart Citations